2011
DOI: 10.2165/11594170-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Cardiovascular Safety of Aromatase Inhibitors in Patients with Early Breast Cancer into Perspective

Abstract: In the adjuvant setting, the third-generation aromatase inhibitors (AIs) anastrozole, letrozole and exemestane are recommended at some point during treatment, either in the upfront, switch after tamoxifen or extended treatment setting after tamoxifen in postmenopausal patients with hormone receptor-positive early breast cancer. AIs have demonstrated superior disease-free survival and overall benefit-to-risk profiles compared with tamoxifen. Potential adverse events, including cardiovascular (CV) side effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…As reported in a recent systematic review, treatment with AIs did not correlate with any definitive change or unfavorable effect on plasma lipoproteins [30], and in a sub-study of Japanese women from the Tamoxifen Exemestane Adjuvant Multinational (TEAM) trial, exemestane or anastrozole treatment had no clinically significant effect on serum lipids in postmenopausal women with hormone-receptor-positive breast cancer [31]. Musculoskeletal symptoms and decreased bone mineral density are anticipated effects of hormonal therapies, such as AIs, that produce menopause-like effects [32].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As reported in a recent systematic review, treatment with AIs did not correlate with any definitive change or unfavorable effect on plasma lipoproteins [30], and in a sub-study of Japanese women from the Tamoxifen Exemestane Adjuvant Multinational (TEAM) trial, exemestane or anastrozole treatment had no clinically significant effect on serum lipids in postmenopausal women with hormone-receptor-positive breast cancer [31]. Musculoskeletal symptoms and decreased bone mineral density are anticipated effects of hormonal therapies, such as AIs, that produce menopause-like effects [32].…”
Section: Discussionmentioning
confidence: 74%
“…Although results from two meta-analyses reported a higher risk of cardiovascular AEs associated with AIs compared with tamoxifen, these data have not been confirmed in a placebo-controlled trial, and available data do not support a substantial risk of ischemic cardiovascular events associated with AI treatment or differences in the risk of cardiovascular events for the different AIs [29, 30, 3639]. Studies with longer follow-up time are needed to further define the cardiovascular safety profile of AI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of HDL as a cardioprotective factor is not as strong as previously thought, (44) but there are still concerns about the potential increase in cardiovascular risk in this healthy population. Younus et al (45) evaluated 22 papers that reported data regarding cardiovascular event incidence in women taking AIs from 8 randomized control trials. To date, no studies have shown that AIs increase cardiovascular risk but follow-up has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase inhibitors (AIs), which are used clinically for treatment of breast cancer, carry the potential risk of increased cardiovascular events (5,22,28), in part mediated by the favorable effects of estrogen on plasma lipids (61) and vascular endothelial function (28). Although the link between the use of AIs and cardiovascular disease risk is still under investigation (33), aromatase gene polymorphisms in the human population have been shown to influence stroke and cardiovascular disease risk in a sexually dimorphic manner.…”
mentioning
confidence: 99%